About the automation of procedures to assess the operation parameters of by-pass turbojet engines (BTJE) - B. A. Chichkov (Научный вестник МГТУ ГА, 2023)
During aircraft operation, the assessment of operation parameters with the different use of nomograms is completed. This approach is prevalent in the operation of aviation gas-turbine engines as part of aircraft power plants. In this case, for example, the assessment of engine operation parameters on the ground, depending on environmental conditions prior to start-up and run-up, is required. Reducing working hours of the aircraft power plants maintenance can be provided by the automation of the denoted procedures which purpose is the formation of the applicable list of values for assessed parameters while assigning available environmental conditions considering the required restrictions. To allow for the visualization and familiar conceptions of carried out assessments, it is advisable not to be limited to only documenting quantitative parameter estimations but also to provide them with graphical representations. The purpose of the article is not aimed at describing a complete algorithm of the engine operation parameters assessment but demonstrating a solution capability for the automation of the procedures for the engine operation parameters assessment on the ground as the task of search for a solution in the restricted conditions using the approximation 30 apparatus and piecewise approximations by the method of the smallest squares and the correlation criterion of significance. The examples of quantitative estimations for one of mass domestic engines are given. The described approach is applicable to a broad list of engines due to the common character of algorithms for the parameter assessment using nomograms. Software based on the tabular calculation processor from the LibreOffice package, Apache-licensed free software, is cross-platform.